Aspectos da Energética de Wilhelm Ostwald (1853-1932) - Frascari, Alexandre (2020)
Friedrich Wilhelm Ostwald (1853-1932) was a professor of chemistry at the University of Leipzig who proposed an organization of science based on energy. Ostwald won the Nobel Prize In 1909 for his work on catalysis. At the end of the nineteenth century, his proposal to consider energy as a fundamental concept in unifying all fields of knowledge initiated a movement against scientific materialism. For Ostwald, energy was analogous to the metaphysical notion of substance, meaning everything that remains in the midst of change. Ostwald justified the metaphysical concept of substance, not from a philosophical view, but from sensory experience. He organized scientific knowledge according to a pyramidal structure that classified sciences according to their degree of abstraction. In this respect, he placed the formal sciences, such as logic, arithmetic and geometry and movement at the base of the pyramid, moving on up through the physical sciences until reaching the top to find the life sciences of physiology, psychology and sociology. This research on Ostwald's work was approached from an epistemological, historiographic and social context, therefore placing Ostwald in confrontation with the scientific and philosophical movements of the time, which were concerned with whether atoms existed or not, as well as the elaboration of scientific atomic models. During this period, the word “Kraft” used in German texts in reference to the principle of conservation and translated as force, became the concept of energy widely used by Ostwald. There was a first energetic movement, which Ostwald expanded from the concept of mechanical energy into other fields of physics through thermodynamics. Finally, Ostwald can be seen as a continuator of this movement, which has further universalized the use of the concept of energy